A MEASUREMENT OF THE D0 LIFETIME - Althoff, M; Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Rosskamp, P; Wallraff, W; Bock, B; Eisenmann, J; Fischer, H; Hartmann, H; Jocksch, A; et al. (Springer-Verlag, 1986)
We have determined the D0 lifetime from reconstructed vertices of D0 mesons produced in e+e- annihilations at an average center of mass energy of 42.2 GeV. From fifteen events the D0 lifetime was determined to be (4.3-1.4+2.0±0.8)×10-13s. © 1986 Springer-Verlag.